Efficacy and safety of anlotinib in patients with desmoid fibromatosis: a retrospective analysis - Xie, Mengzhang; Huang, Qi; Gong, Taojun; Wang, Yitian; Li, Zhuangzhuang; Lu, Minxun; Luo, Yi; Min, Li; Zhou, Yong; Tu, Chongqi (Frontiers in Oncology, 2024)
Desmoid fibromatosis is a formidable fibroblastic neoplasm known for its heightened tendency for local recurrence. Anlotinib, a novel multitargeted angiogenesis inhibitor, represents a novel approach for targeted therapy. We retrospectively enrolled 66 patients. Anlotinib was initiated at a daily dose of 12 mg and adjusted based on drugrelated adverse effects. Progression-free survival was the primary endpoint. In total, sixty-six (25 men and 41 women) consecutive patients were enrolled. No patients achieved a complete response; however, fourteen patients (21.21%) exhibited a partial response, while forty-six patients (70%) experienced disease stability.Progressive disease was observed in 6 patients (9.10%), and the progression-free survival rates at 12 and 36months were 89.71% and 82.81%, respectively. The disease control rate was 90.91%, while the objective response rate was 21.21%. Anlotinib is effective in managing recurrent and symptomatic patients with desmoid fibromatosis. Our results also suggested that postoperative anlotinib may reduce recurrence. However, it's toxicity is associated with a Anlotinib in Desmoid Fibromatosis 3 greater risk of hand-foot skin reaction and hypertension. Therefore, given that 41.67% of patients were subjected to dose adjustments associated with the initial dose of 12 mg, implementing dosage reductions may help balance efficacy with side effects.